2010
DOI: 10.1371/journal.pone.0008960
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Is an Oncogene Activated by Recurrent 3q26.3 Amplifications in Human Lung Squamous Cell Carcinomas

Abstract: Squamous cell carcinoma (SCC) of the lung is a frequent and aggressive cancer type. Gene amplifications, a known activating mechanism of oncogenes, target the 3q26-qter region as one of the most frequently gained/amplified genomic sites in SCC of various types. Here, we used array comparative genomic hybridization to delineate the consensus region of 3q26.3 amplifications in lung SCC. Recurrent amplifications occur in 20% of lung SCC (136 tumors in total) and map to a core region of 2 Mb (Megabases) that encom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
230
2
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 279 publications
(256 citation statements)
references
References 64 publications
(95 reference statements)
20
230
2
4
Order By: Relevance
“…11 Besides its role during neurogenesis and embryonic foregut development, SOX2 can aid the reprogramming of adult cells into induced pluripotent stem cells, indicating a major potency for induction of cellular fate changes. 12,14,28 More recently, studies have identified SOX2 as the driving gene of the well-known 3q amplicon in squamous cell carcinomas of the lung and the esophagus, suggesting SOX2 as a novel candidate oncogene 9,10 in lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Besides its role during neurogenesis and embryonic foregut development, SOX2 can aid the reprogramming of adult cells into induced pluripotent stem cells, indicating a major potency for induction of cellular fate changes. 12,14,28 More recently, studies have identified SOX2 as the driving gene of the well-known 3q amplicon in squamous cell carcinomas of the lung and the esophagus, suggesting SOX2 as a novel candidate oncogene 9,10 in lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,17 These variations in frequency are most likely due to methodological discrepancies applied by different laboratories (eg the molecular method applied for detection of SOX2 copy number status and the threshold set to distinguish between different levels of amplification). Furthermore, differences between the cohorts and tumor heterogeneity have to be considered.…”
Section: Sox2 In Lung Squamous Cell Carcinomasmentioning
confidence: 99%
See 3 more Smart Citations